EFEK DOMINO INDUSTRI 4.0 : PELUANG DAN ANCAMAN USAHA TERNAK SAPI PERAH - Amam Amam; Pradiptya A. Harsita; Soetriono Soetriono (UPT Penerbitan Universitas Jember, 2018)
A research was carried out to find the opportunity factors and threats factors of dairy cattle business in Pujon District, Malang Regency. The data was collected in the period of August-October 2018 using a survey method for 105 dairy farmers. Data was processed using SEM (Structural Equation Model) analysis with the SmartPLS 2.0 application. The findings of the research show that dairy farmers livestock human resources was positively influenced by group dynamics (0.213) and vulnerability context (0.108) and was negatively influenced by farming business development (-0.215). The conclusion of this research is the opportunity factors was derived from business development and improving the quality of dairy farmers livestock human resources, while threat factors was derived from group dynamics and vulnerability context.